Comparing the Quality of Life and the Ability to Perform Daily Activities in Elderly and Middle-Aged Monocular Veterans - Minooiefar J.; M. Ghasemi Borumand; M. Masoumi; H. Haghani; R. Sahaf (Afarand Scholarly Publishing Institute, 2019)
Aims: Aging is an inevitable part of human life, which is associated with reduced ability, increased dependence, and susceptibility to a variety of diseases. Those who experience this period with previous long-term injuries are exposed to more difficulties. The aim of this study was to compare the quality of life and the ability to perform daily activities in elderly and middle-aged monocular veterans. Instruments & Methods: This descriptive cross-sectional study was conducted in 2015 among 1271 monocular veterans in 19 provinces of the country, who were selected by available sampling. The participants were divided into two groups: middle-aged (between 40 and 59 years) and elderly (60 years and older). The research tools were quality of life, activities of daily living (ADL), and instrumental activities of daily living (IADL). The data were analyzed by SPSS 23 software, using independent t-test and Mann-Whitney test. Findings: The mean age of the middle-aged and elderly veterans was 46.3±4.1 and 68.7±7.9 years, respectively. There was a significant difference in vitality (p=0.002), physical functioning (p<0.001) and limitation in role physical (p=0.003) between two groups .In ADL, in both groups, the least independence was related to transfer and mobility on uneven surfaces. Except for the bowel control, there was a significant difference between two groups on all activities (p<0.001). In IADL, the highest dependency was on laundry and except for housekeeping, there was a significant difference between the two groups in all areas (p<0.05). Conclusion: The levels of quality of life, the ability to perform daily activities, and instrumental daily activities are lower in elderly monocular veterans compared to the middle-aged group.